Makna Keadilan Tuhan Bagi Orang Yang Tulus Hati : Berdasarkan Kitab Mazmur 41 - Widodo, Agus (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2023)
Abstrack The meaning of God's justice for those who are sincere is based on psalm 41. Sincerity is a condition that is truly and clean in heart, that is holy, honest, straight, pure without pretending. What is in the heart is the same as what is spoken. Not being hypocritical, having integrity, having no agenda or self-interest in doing something. A sincere person does not have malicious intentions towards others. Sincere is like a dove. Wise as serpents and as pure as doves. Sincere is a clean nature without strings attached. In Psalm 41, God saw David and called David a sincere person. Keyword: David, justice, sincere